A prospective study of the relationship between psychological factors and breast cancer - Tso-Ying Lee; Mei-Ling Yeh (Elsevier, 2016)
Objective: This cross-sectional prospective study aimed to explore the relationship between psychological factors and breast cancer incidence. Methods: The subjects who scheduled to receive mammography screening were recruited from a medical center's outpatient department in Taiwan. Psychological factors used for measurement were stress, anxiety, and depression. Results: A total of 1160 questionnaires were completed, which underwent statistical analysis using independent t-test, Chi-square test, Pearson's correlation, and multiple logistic regression. There were statistically significant differences in the average scores of the two groups with and without breast cancer for psychological factors of anxiety (t = −2.071; P = 0.039), depression (t = −3.035; P = 0.002), and stress (t = −4.087; P < 0.001). The crude odds ratio of the two groups showed that subjects with borderline anxiety were 2.576 times ( P = 0.001) more likely to have breast cancer as compared to subjects with no anxiety. Subjects with depression were 4.078 times (P = 0.03) more likely to have breast cancer as compared to subjects with no depression. Every point added to the average total stress score increased the additional risk of breast cancer by 1.124 times (P < 0.001). Conclusions: After making adjustments on educational factors, the results conclude that psychological factors such as stress, anxiety, and depression can be considered predictors of breast cancer risk. To prevent and control breast cancer in women, the findings suggest that nurses should consider adding emphasis on psychological factors in women's health education.